Rowing injuries in elite athletes: A review of incidence with risk factors and the role of biomechanics in its management - Arumugam, S.; Ayyadurai, P.; Perumal, S.; Janani, G.; Dhillon, S.; Thiagarajan, K. A. (Indian Journal of Orthopaedics, 2020)
Rowing is an Olympic sport gaining popularity in India and injuries are common in these athletes. Determinants of performance, injury risk and training are all interrelated in rowing. Injuries result from various risk factors including fitness issues and improper techniques. Rowers should have adequate leg extension strength and lumbo-pelvic coordination to produce and transmit power from the legs to the oar handle. Biomechanical analysis of the rowing stroke can help in preventing injuries and optimise technique for best performance. It involves a detailed and systematic observation of movement patterns to establish the quality of the movement and provide feedback to the rower about the key variables affecting performance and injury risk. Kinetics such as foot forces and kinematics such as key joint angles can be accurately measured by instrumented foot stretcher and three-dimensional motion capture. Aim